Da incompletude da linguagem na materialidade metálica - Schmitt, Michele (2006)
The research problem we propose to reflect about concerns the constitution of language and of memory in the metallic materiality. We focus, in our work, on the fact that technologies are produced by man, under certain social and historical conditions. The fact that language may be conceived externally to man in informatic media -, does not mean that it is in a transcendental plan in relation to the subject, to the discourse. Furthermore, what is from the historical subject belongs as well to the machine, to the technique. Our point of view, thus, is that technique and man, language and subject should be thought as mutually constituted and not as opposite elements, which would exclude each other. In this way, we propose, under the perspective of French Discourse Analysis, a study of language that takes in consideration that language and discourse are mutually constituted. Our aim is to emphasize that the order of language is not independent from the order of discourse. By observing the working of formalization and of the categories of time and space in Google, we infer that there is a double movement of sense constitution in the metallic materiality: on the one hand, a movement that searches the completeness of language, which would be possible through the constitution of a memory with a large capacity of storage; in this memory, senses would be frozen in space and time, so that the irruption of other significations would not become possible. On the other hand, incompleteness is constituted in the simulation of completeness itself. We think incompleteness is structured by the excess of information that circulates in Web. This excess is a sign that there is ever something to be said, since language is not a representation of the world.